9ab-6a+5b-3=

Simple and best practice solution for 9ab-6a+5b-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9ab-6a+5b-3= equation:


Simplifying
9ab + -6a + 5b + -3 = 0

Reorder the terms:
-3 + -6a + 9ab + 5b = 0

Solving
-3 + -6a + 9ab + 5b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + -6a + 9ab + 3 + 5b = 0 + 3

Reorder the terms:
-3 + 3 + -6a + 9ab + 5b = 0 + 3

Combine like terms: -3 + 3 = 0
0 + -6a + 9ab + 5b = 0 + 3
-6a + 9ab + 5b = 0 + 3

Combine like terms: 0 + 3 = 3
-6a + 9ab + 5b = 3

Add '-5b' to each side of the equation.
-6a + 9ab + 5b + -5b = 3 + -5b

Combine like terms: 5b + -5b = 0
-6a + 9ab + 0 = 3 + -5b
-6a + 9ab = 3 + -5b

Reorder the terms:
-3 + -6a + 9ab + 5b = 3 + -5b + -3 + 5b

Reorder the terms:
-3 + -6a + 9ab + 5b = 3 + -3 + -5b + 5b

Combine like terms: 3 + -3 = 0
-3 + -6a + 9ab + 5b = 0 + -5b + 5b
-3 + -6a + 9ab + 5b = -5b + 5b

Combine like terms: -5b + 5b = 0
-3 + -6a + 9ab + 5b = 0

The solution to this equation could not be determined.

See similar equations:

| b+9+6b-9= | | 3x+11=-7+x | | 3sinx=-1.2 | | 22=7.34+b | | 2m-10+5m-80=180 | | 2(3s+6)=32 | | 4z+3-9x= | | 2k+9k= | | 8x+8=2x+3 | | y=2xy+6y-10 | | 16.95=1/x | | 5(4+2x)+2x=176 | | 3+2m-7=10 | | Y2=-1/4x | | 9x-(2x-10)=40 | | 0.5=8/x | | 4(x+6)=20x-7 | | X=112+-3x | | 7x=-26 | | 3x=146 | | 4x+24=2x-7 | | 45c^6+20c^4= | | 10xy+8x+25y+20=0 | | 6y-9=3(y+5) | | 15x+64=302 | | 7d=-21 | | 0=9x-56 | | 7t-9=3(y+5) | | (7u-5)^1/2=(9u-15)^1/2 | | 3x+63=84 | | y=-px+q | | 0.09Xx=144.39 |

Equations solver categories